2018
DOI: 10.1016/j.jcmgh.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic Escherichia coli EspH-Mediated Rho GTPase Inhibition Results in Desmosomal Perturbations

Abstract: Background & AimsThe diarrheagenic pathogen, enteropathogenic Escherichia coli (EPEC), uses a type III secretion system to deliver effector molecules into intestinal epithelial cells (IECs). While exploring the basis for the lateral membrane separation of EPEC-infected IECs, we observed infection-induced loss of the desmosomal cadherin desmoglein-2 (DSG2). We sought to identify the molecule(s) involved in, and delineate the mechanisms and consequences of, EPEC-induced DSG2 loss.MethodsDSG2 abundance and locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…15 We recently reported that enteropathogenic Escherichia coli (EPEC) perturbs desmosomes. 16 EPEC effector protein EspH, via its Rho GTPase inhibitory function, induces keratin IF retraction and desmosomal disruption. Beyond EPEC pathogenesis, our studies provide insights on how desmosomes are maintained, particularly in the intestines, and expand our knowledge of the role of Rho GTPases in desmosomal assembly and stability.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…15 We recently reported that enteropathogenic Escherichia coli (EPEC) perturbs desmosomes. 16 EPEC effector protein EspH, via its Rho GTPase inhibitory function, induces keratin IF retraction and desmosomal disruption. Beyond EPEC pathogenesis, our studies provide insights on how desmosomes are maintained, particularly in the intestines, and expand our knowledge of the role of Rho GTPases in desmosomal assembly and stability.…”
mentioning
confidence: 99%
“…Consistent with a role for Rho-mediated actin polymerization in the maintenance of keratin IFs in intestinal epithelial cells, we observed that the actin-stabilizing compound jasplakinolide rescues infected cells from EPEC-induced keratin retraction. 16 But how does keratin retraction promote desmosomal plaque protein loss? Is the half-desmosome pulled into the cytoplasm while still tethered to the keratin IF, or does keratin dissociate from the desmosome prior to internalization and degradation of the desmosomal plaque components?…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, Roxas et al 4 investigated the impact of EPEC on desmosome disruption in the intestinal epithelia. They examined the contribution of EspH and Rho GTPase signaling to the loss of intestinal epithelial integrity.…”
mentioning
confidence: 99%